Caracterização populacional em camarões marinhos Rimapenaeus constrictus (Stimpson, 1874), utilizando marcadores microssatélites e análises morfométricas - Silva, Thiago Buosi (2007)
Shrimp capture is one of the most important fishing activities and has been growing in the last years due to an increment in the fishing effort and the larger number and enhanced fishing power of the shrimp boats. Thus, most of the penaeid stocks are being threatened by overexploitation. For our object of study we used the marine shrimp species Rimapenaeus constrictus, captured off the coast of Guarapari, Espírito Santo and the coast of Ubatuba, São Paulo. These points were strategically chosen since they are located above and below the Cabo Frio upwelling, a potential geographic barrier for the dispersion of marine organisms. Genetic studies, through the development and analysis of molecular microsatellite markers, and morphometric studies were performed in order to determine if there is any structure in the populations of this region. The HE and HO values of the four developed polymorphic microsatellite loci were 0.502 and 0.283 for Ubatuba and 0.473 and 0.374 for Guarapari. The FST estimate between the populations (0.0012; p = 0.1500) and probability (Bayesian method; p = 0.993) indicate that these populations behave as a single one, contrasting with the results of the multivariate analyses of the morphometric data. The gene flow rate between the populations may be attributed to the pronounced larval dispersion led by the surface current system of the Brazilian coast. Different patterns of growth and weight gain may have been responsible for the structure based on the morphometric data. Although a raise in the sample and microsatellite numbers are necessary, this study was valuable as it produced knowledge that is useful for the conservation of this species.